The association between social support and posttraumatic stress symptoms among survivors of betrayal trauma: a meta-analysis - Vanessa Tirone; Daria Orlowska; Ashton M. Lofgreen; Rebecca K. Blais; Natalie R. Stevens; Brian Klassen; Philip Held; Alyson K. Zalta (European Journal of Psychotraumatology, 2021)
Background: Betrayal traumas have a particularly deleterious effect on mental health. Although social support is a robust predictor of posttraumatic stress disorder (PTSD) symptom severity, it is not clear what factors may impact this relationship among betrayal trauma survivors. Objective: This study sought to describe the association between social support and PTSD symptom severity among survivors of betrayal trauma and examine whether methodological, sample, trauma, and social support characteristics moderated this association. Method: A comprehensive search identified 29 studies that assessed the cross-sectional association between PTSD symptom severity and social support among 6,510 adult betrayal trauma survivors. Results: The average effect size (r = −.25; 95% CI: −.30, −.20) was small to medium, with significant heterogeneity between studies (I2 = 71.86). The association between PTSD and social support was stronger when the trauma was perpetrated by a romantic partner compared to mixed perpetrators, even after accounting for covariates. There was also a significant effect of support type depending on whether the support was provided in the context of trauma disclosure. Specifically, positive reactions to trauma disclosure were not associated with PTSD symptoms whereas general positive social support (not disclosure focused) was associated with fewer PTSD symptoms. Negative reactions to trauma disclosure were associated with more PTSD symptoms. None of the included studies measured general negative social support outside of trauma disclosure. Conclusions: Our findings suggest that social support may be a particularly important buffer against PTSD symptoms when experiencing traumatic betrayal by an intimate partner. Additionally, our results suggest that social support interventions for those experiencing betrayal trauma should focus on reducing negative responses to disclosure and bolstering general satisfaction with social support.